Lower-body power in boxers is related to activity during competitive matches - Rimkus, L.; Satkunskiene, D.; Kamandulis, S.; Bruzas, V. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to create an activity profile of high-level boxing performance and to identify associations between boxers` lower-body power capabilities and their activity profile. Eight high-level boxing athletes participated in the study. Lower-body power capabilities were calculated from counter-movement jumps (CMJs) and squat jumps (SJs) using a force plate. The boxing performance analysis consisted of 30 different variables gathered from 18 bouts from various international matches. The results demonstrated that boxing athletes delivered 22.3 ± 5.3 punches per min. The effectiveness of head punches was 14.3 ± 3.9%. CMJ height was correlated with the total number of punches thrown to the body and SJ height with rear-hand hooks (r = 0.735 and r = 0.793, respectively). The rate of SJ force development was correlated with the straight rear-hand punches (r = 0.751) and head punches effectiveness (r = 0.750). SJ peak power was inversely correlated with total stop frequency (r = - 0.786). In conclusion, the athletes who displayed higher power values in the CMJ and SJ tests were also more active during competitive bouts and accumulated less stoppage time during the competitive boxing bouts. More explosive boxers had higher effectiveness of head punches.